Analysis of the model reactor dynamics - Bučys, Kostas; Švitra, Donatas (Lietuvos matematikos rinkinys, 1999)
There is constructed a model of nuclear reactor dynamics with delay in feedback line "powerreactivity" including six groups of delayed neutrons. Using D-partitioning method there is analysed the characteristic quasi-polynomial disposition of roots on complex plane.